Food, Inc.. 2 : inside the quest for a better future for food - Weber, Karl, 1953- (PublicAffairs, 2023)
This companion book to the sequel of 2008's award-winning documentary Food, Inc. examines the latest remarkable developments to reverse our dysfunctional food system through the efforts of brilliant innovators, scientists, journalists and activists.